Temporal dynamics in the daily lives of health practitioners. (November 2019) - Wang, Cynthia
The working days of health practitioners are long and often hectic. This paper examines the minutiae of how health practitioners, particularly physicians and nurses, organize their time throughout the day. Through in-depth interviews of attending physicians, medical residents, and nursing staff at a major urban teaching hospital in California, I explore the daily dynamics of temporality within the lives of health practitioners, from the point of view of health practitioners, and consider the structures of power that are evident, and I do this through the lens of time and temporality. My studies have found that, whereas individuals may be able to control the time of other individuals who are lower on the hierarchy than themselves, institutional obligations and ritualized cultural practices that colonize individual time, and indeed, normalize certain temporal rhythms and expectations often trump these individual dynamics. While the specific site of this study was focused on the health care field, the broader themes of how social and organizational power manifests through the negotiation of time are relevant to many other sites of inquiry, particularly within monochronic societies which perceive time as a commodity.